Analysing Work-Life Balance in Hospitality Industry: Mandapa Employees’ Perspective in Bali, Indonesia - Adyatma, Prastha (Journal of Hotel Management, 2023)
This dissertation focuses on exploring work-life balance in the hospitality industry in Bali, Indonesia from the employees' perspective. The study aims to investigate the definition and elements of work-life balance and its potential implementation in the industry. The research employs a primary qualitative research approach where five actively employed hospitality workers, aged between 23 and 36, with diverse marital status, hierarchy, and departments were interviewed. Thematic analysis was used to analyze the data, which was compared with previous literature on work-life balance. The findings indicate that work-life balance is present for four participants and missing for one. Moreover, the study highlights that hierarchy and marital status impact employees' work-life balance, while culture strongly influences female employees. Additionally, long hours, overtime, and inconsistent schedules were identified as negative consequences of working in the hospitality industry. However, due to the limited sample size and broad demographic range, no definitive conclusions can be drawn. Therefore, this report offers a general discussion on work-life balance in the hospitality industry rather than a specific demographic.